Phaleria macrocarpa (Scheff.) Boerl. in Ethnopharmacology: Pharmacognosy, Safety, and Drug Development Perspectives - Anandarajagopal Kalusalingam; Kamaliah Kamal; Abdullah Khan; Bama Menon; Ching Siang Tan; Venkateshan Narayanan; Sattanathan Kumar; Khang Wen Goh; Kah Seng Lee; Jactty Chew; Long Chiau Ming (Progress in Microbes and Molecular Biology)
Phaleria macrocarpa, a medicinal plant from the Thymelaceae family, is predominantly found in Malaysia and Indonesia. This review aims to comprehensively summarize the phytochemical, pharmacological, and toxicological aspects of P. macrocarpa, along with modern approaches and safety concerns. Data for the review were collected from various scientific databases and relevant literature on P. macrocarpa. The review discusses the plant's phytochemical composition and its diverse medicinal properties, including anti-inflammatory, antihypertensive, antidiabetic, antioxidant, antimicrobial, antipyretic, antiulcer, antiviral and anticancer activities. P. macrocarpa has also been used to treat various female health conditions. Additionally, combination therapies and advanced drug delivery systems such as nanoemulsion have been reviewed. These pharmacological activities are attributed to the plant's phytoconstituents. The review will be valuable for researchers involved in medicinal plant research and drug discovery, offering potential for use alongside modern therapeutic agents. However, clinical studies are essential to validate its therapeutic applications. Further research is required to develop standardized herbal pharmaceuticals from P. macrocarpa that are effective, safe, and meet regulatory standards for quality assurance.